2020
DOI: 10.3390/ijerph17197275
|View full text |Cite
|
Sign up to set email alerts
|

Operating Theatre Ventilation Systems and Their Performance in Contamination Control: “At Rest” and “In Operation” Particle and Microbial Measurements Made in an Italian Large and Multi-Year Inspection Campaign

Abstract: In Operating Theatres (OT), the ventilation system plays an important role in controlling airborne contamination and reducing the risks of Surgical Site Infections (SSIs). The air cleanliness is really crucial in this field and different measurements are used in order to characterize the situation in terms of both airborne microbiological pollutants and particle size and concentration. Although the ventilation systems and airborne contamination are strictly linked, different air diffusion schemes (in particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…22,70,110,99,100,102,103,[106][107][108][109] Eight articles included microbial contamination in the operating room as one of the recorded outcomes, although the specific ventilation systems under study varied between articles. 22,70,99,[106][107][108][109][110] Similar to the literature on LAF, there was a general consensus that microbial contamination is lower in operating rooms equipped with unidirectional airflow as opposed to turbulent and mixed airflow systems, regardless of how this was measured (i.e., active versus passive sampling methods). Those studies that compared mixed and turbulent airflow systems found that the microbial contamination is often very similar, and any differences tend not to be statistically significant.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…22,70,110,99,100,102,103,[106][107][108][109] Eight articles included microbial contamination in the operating room as one of the recorded outcomes, although the specific ventilation systems under study varied between articles. 22,70,99,[106][107][108][109][110] Similar to the literature on LAF, there was a general consensus that microbial contamination is lower in operating rooms equipped with unidirectional airflow as opposed to turbulent and mixed airflow systems, regardless of how this was measured (i.e., active versus passive sampling methods). Those studies that compared mixed and turbulent airflow systems found that the microbial contamination is often very similar, and any differences tend not to be statistically significant.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Of the 46 studies on OR ventilation that were based on empirical data, 22 did not investigate LAF. 7,22,[98][99][100][101][102][103][105][106][107][108]46,109,110,53,66,70,[94][95][96][97] It is important to note that the conflicting way in which authors use the term "unidirectional airflow" may have led to an underestimate of the number of papers that investigated LAF. Some authors equate unidirectional airflow with LAF and use these terms interchangeably, while others do not; some studies explicitly differentiate between the two.…”
Section: Empirical Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lidwell et al carried on their work, showing that ultra-clean air (ie, <10 colony-forming units (CFUs)/m 3 ) in combination with body-exhaust suits and prophylactic antibiotics further improved infection rates 8–10. Based on their work, in combination with several reports showing that laminar air flow (LAF) reduces bacterial contamination in the OR air,11–13 many ORs are today equipped with LAF ventilation. Unfortunately, though, when evaluated in large cohort studies, systematic reviews and meta-analyses, LAF systems in modern state-of-the-art ORs have so far failed to prove efficient in preventing infections, compared with conventional ventilation 14–19…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have investigated compliance with air quality standards and management of ORs [17][18][19], and none, to the best of our knowledge, have identified factors associated with the management of air quality in clean ORs in China. erefore, the aim of this study was to survey the usage, maintenance, and testing of ventilation systems in clean ORs among hospitals in China with the use of an online questionnaire.…”
Section: Introductionmentioning
confidence: 99%